2001
DOI: 10.1097/00005537-200104000-00021
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Quality of Life in Head and Neck Cancer Patients. Part I: At Diagnosis

Abstract: The chosen questionnaires differentiated between different sites of head and neck cancer at diagnosis. Tumor stage had the most powerful impact on HQL score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
152
9
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(189 citation statements)
references
References 41 publications
26
152
9
2
Order By: Relevance
“…The results of this specific patient-rated physical domain of swallowing at 2 years post AFRT-CB is in contrast with the previously reported data for heterogenous HNC patients which have reported improving global function on the EORTC-QLQ-C30 scale by 12 months post-treatment (13)(14)(15)(16)(17). Furthermore, overall patient-rated functional outcomes (using the FACT-H&N) have also been found improve to pretreatment levels by 12 months posttreatment following a hyperfractionated , accelerated regimen (18).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of this specific patient-rated physical domain of swallowing at 2 years post AFRT-CB is in contrast with the previously reported data for heterogenous HNC patients which have reported improving global function on the EORTC-QLQ-C30 scale by 12 months post-treatment (13)(14)(15)(16)(17). Furthermore, overall patient-rated functional outcomes (using the FACT-H&N) have also been found improve to pretreatment levels by 12 months posttreatment following a hyperfractionated , accelerated regimen (18).…”
Section: Discussioncontrasting
confidence: 99%
“…This pattern of long term adjustment has been found previously (13)(14)(15)(16)(17)(18). In the current cohort, head and neck specific concerns such as cosmesis, voice and communication, and the presence of pain significantly improved from 6 months to 2 years post-treatment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In their study females had a slight tendency to score worse than males for some functioning scales with symptoms, financial difficulty and sexuality. Hammerlid et al (2001a) found that females scored worse than males for some areas at diagnosis, in particular, in emotional functioning. These conflicting results on gender differences cannot easily be explained, but overall, gender does not seem to have a major influence on HRQL during radiation treatment -the decline seems to be similar in the two sexes.…”
Section: Discussionmentioning
confidence: 88%
“…The EORTC QLQ-H&N35 is widely used to measure quality of life in H&N cancer patients (Singer et al, 2013). Both prospective and cross-sectional studies (Bjordal et al, 2001;Hammerlid et al, 2001aHammerlid et al, , 2001bHammerlid et al, , 2001cNguyen et al, 2002;Talmi et al, 2002;Shepherd and Fisher, 2004) have documented reductions in HRQOL in populations of H&N cancer patients who have received RT. Several studies have also examined changes in HRQOL during the treatment period (Bjordal et al, 2001;Henson et al, 2001; Airolldi et al, 2004;Parliament et al, 2004;Jabbari et al, 2005; Braam et al, 2007; Curran et al, 2007; Ackerstaff et al, 2009; Ackerstaff et al, 2012;Maguire et al, 2011;Maurer et al, 2011;Nutting et al, 2011).…”
mentioning
confidence: 99%